2012
DOI: 10.1158/1940-6207.capr-12-0048
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Ovarian Cancer Survival: A Systematic Review and Meta-analysis

Abstract: Studies that have examined the association between obesity and ovarian cancer survival have provided conflicting results. We reviewed and quantitatively summarized existing evidence, exploring potentially important sources of variability, such as the timing of body mass index (BMI) assessment and different cutpoints used to categorize BMI. A systematic search of MEDLINE and EMBASE was conducted to identify original data evaluating the association between obesity and survival in women with ovarian cancer. Adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
86
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 49 publications
3
86
0
3
Order By: Relevance
“…Mortality after ovarian cancer is 17% (95%CI: 3-34%) higher among obese compared to non-obese women [59]. Although the number of studies is still small, there is emerging evidence that higher BMI is associated with poorer cancer-specific mortality from endometrial cancer [60].…”
Section: Body Weight In Cancer Survivorsmentioning
confidence: 99%
“…Mortality after ovarian cancer is 17% (95%CI: 3-34%) higher among obese compared to non-obese women [59]. Although the number of studies is still small, there is emerging evidence that higher BMI is associated with poorer cancer-specific mortality from endometrial cancer [60].…”
Section: Body Weight In Cancer Survivorsmentioning
confidence: 99%
“…Si bien dicha terapia ha sido asociada generalmente como un factor de riesgo del cáncer de ovario 19 , un meta-análisis establece que no observaron diferencias entre IMC y cáncer de ovario entre mujeres post-menopáusicas que utilizaron terapia de reemplazo hormonal y las que no. Este estudio, además, establece que la obesidad aumenta el riesgo de desarrollar los cáncer de ovario histológicamente menos frecuentes (serosos que presentan un alto grado de agresividad y los borderline) y, finalmente, los autores concluyen que un bajo IMC no previene la letalidad del cáncer de ovario, por lo tanto, no actuaría como un factor protector 15 .…”
Section: Tejido Adiposo Y Su Asociación Con Cáncer De Ovariounclassified
“…En concordancia con esto, un estudio poblacional muestra que las mujeres obesas que no utilizan terapia de reemplazo hormonal tienen un riesgo mayor (80%) de desarrollar cáncer de ovario respecto a las mujeres de peso normal 13 . Finalmente, lo anterior se relaciona con un meta-análisis reciente donde se encuentra que las personas no obesas tendrían una mejor sobrevida al cáncer de ovario versus las obesas y que esta asociación podría relacionarse con las características histológicas del cáncer 14,15 .…”
unclassified
“…African American women are nearly twice as likely to be obese as non-Hispanic white women (59% vs. 32%), 3 and a growing body of evidence suggests that obesity is associated with both ovarian cancer risk and survival. [4][5][6] Meta-analyses and pooled analyses conducted among predominantly white populations have concluded that overweight and obese women are at increased risk for ovarian cancer 4,5 and have poorer survival after an ovarian cancer diagnosis. 6 For African American women, some 7,8 but not all 9 studies suggest obesity is a risk factor for ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Meta-analyses and pooled analyses conducted among predominantly white populations have concluded that overweight and obese women are at increased risk for ovarian cancer 4,5 and have poorer survival after an ovarian cancer diagnosis. 6 For African American women, some 7,8 but not all 9 studies suggest obesity is a risk factor for ovarian cancer. No studies have specifically addressed the effect of obesity on ovarian cancer survival among African American women.…”
Section: Introductionmentioning
confidence: 99%